Social systems in riverside communities in the Amazon:: socio-environmental dynamics in question - Melo Júnior, Luiz Cláudio Moreira; Sayago, Doris Aleida Villamizar; Tourinho, Manoel Malheiros (Sustainability in Debate, 2017)
This article discusses the recent social-environmental dynamics (2008/2014) of the social systems (family, economic, educational, health and leisure) in riverside communities located in a vast territory of the open frontier along the river Arapiuns, in the western state of Pará. It is a densely forested area that has been targeted since 2010 by the Para government’s public forest concessions policy to the private sector, as part of the Brazilian forestry policy (Law No. 11.284 / 2006). The research was conducted through the application of semi-structured questionnaires with the population of these localities. The main results of the study showed that the social-environmental dynamics of riverside communities were significantly changed since the beginning of forest concession activities in the region.